Single and combined effect of vinyl chloride monomer and high-fat diet on gut microbiota in mice - Yan HAO; Shi-qi CHENG; Xiao-tian ZHAO (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo investigate the impact of vinyl chloride monomer (VCM) alone or in combination with high-fat diet on gut microbe in mice. MethodsTwenty 6-week-old male specific pathogen-free C57BL/6J mice were divided into four groups: control, high-fat diet (40% of fat), VCM (static inhalation of 2 hours at dosage of 800 mg/m3, 5 times per week continuously for 13 weeks), and VCM plus high-fat diet. By the end of treatments, fecal samples were collected from the mice for 16S rDNA sequence analysis to examine alterations of the mice's gut microbe. ResultsThe abundance and community structure of gut microbe changed in the mice with high-fat diet and VCM exposure. In terms of phylum, the ratio of Firmicutes to Bacteroidetes of the mice exposed to VCM and high-fat diet were higher than those of control mice. At genus level, the degree of gut microbes aggregation was different among the four groups. Alpha diversity analysis revealed that the observed gut species of the mice with high-fat diet were inferior to those of the mice of control and VCM plus high-fat diet group (both P < 0.05); the Shannon index for the mice with high-fat diet was significantly lower than that for the mice of other three groups (all P < 0.05). Beta diversity analysis indicated that there were differences in community composition of gut microbes among the four groups. ConclusionExposure to VCM and high-fat diet, alone or combined, could lead to gut microbial imbalance in mice and the combined exposure mainly affect the abundance of gut microbial genera.